Mixed laryngocele: A case report of hoarseness - Cruz, Sara (2011)
Laryngoceles are benign and cystic dilatations of the laryngeal saccule that contains air and communicates with the laryngeal lumen. They are uncommon, and correspond to 5% of begin laryngeal lesions. Classification may be divided as internal, external and mixed, according to their relationships with the thyrohyoid membrane. Dysphonia is the most characteristic symptom, however most are asymptomatic. The authors present a case report of a 67 year old woman with a mixed laryngocele. They briefly review this entity, diagnostics tools and therapeutic approach options.